Implementasi Kurikulum Berbasis Islam di SMP IT Insan Mandiri Kota Sukabumi - Ai Siti Rahmawati; Siti Qamariah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the implementation of an Islamic-based curriculum at SMP IT Insan Mandiri in Sukabumi City. The Islamic-based curriculum is expected to integrate religious values into the learning process to shape students' character, excelling in both religious and academic aspects. This research uses a qualitative approach with a case study method involving observation, interviews, and documentation as data collection techniques. The findings show that the Islamic-based curriculum at SMP IT Insan Mandiri has been implemented effectively, although there are some challenges, such as limited resources and teacher training. Overall, the implementation of this curriculum has successfully contributed to shaping students' character by enhancing their understanding of Islamic values and applying them in daily life. This study is expected to contribute to the development of religious-based education in Islamic schools.Keywords: Implementation of Islamic-based curriculum, SMP IT Insan Mandiri, faith-based education, student character, implementation challenges, educational development.)